2020
DOI: 10.1080/17453674.2020.1853387
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected varus deformity and concomitant metal ion release and MRI findings of modular-neck hip stems: descriptive RSA study in 75 hips with 8 years’ follow-up

Abstract: Background and purpose — Modular-neck hip stems have been identified with corrosion-related problems from the neck–stem junction. We report an ongoing varus deformity of modular-neck hip stems with simultaneous metal ion release observed during a study comparing the migration of modular vs. standard hip stems. Patients and methods — We followed 50 patients with modular and 25 with standard neck stems using radiostereometry (RSA). At 5-year follow-up, we noted a compromised integrity of the modular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(48 reference statements)
1
3
0
Order By: Relevance
“…These damage products may promote ALTR. However, ALTR similar to those described in short/medium-term studies involving mixed-metal NSJs (at least one component made of Co-alloy) [ 9 , 24 , 25 ], have never been reported in the clinical records of this patient cohort. The only case of tissue reaction (metallosis) was likely related neck–rim impingement.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…These damage products may promote ALTR. However, ALTR similar to those described in short/medium-term studies involving mixed-metal NSJs (at least one component made of Co-alloy) [ 9 , 24 , 25 ], have never been reported in the clinical records of this patient cohort. The only case of tissue reaction (metallosis) was likely related neck–rim impingement.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, it is not possible to determine to which extent the NSJ contributes to ion release in vivo. However, the present Ti ion concentration exceeds the range of blood Ti ion concentration (0.6–1.0 µg/l) measured at 5 years for well-working monolithic stem, i.e., Ti-alloy stem including a 36 mm Co-alloy head and crosslinked polyethylene liner [ 22 ]. Therefore, a contribution of the Ti-alloy/Ti-alloy NSJ to blood ion concentration must be acknowledged even in well-working EN hip prostheses, although no significant differences were found in serum Ti ion concentration between EN and monolithic stem design [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 5 - 8 Reported complications of modular stems include increased risk of femoral fracture and stem fractures at the modular junction compared to monoblock stems. 12 , 39 - 41 Feng et al 12 found that their cohort of 108 modular stems had a statistically significant increase in incidence (16.7%) of intraoperative femoral fractures compared to their cohort of 110 nonmodular stems (4.5%; p = 0.004). Similar studies have corroborated these results.…”
Section: Discussionmentioning
confidence: 97%
“…Between March 2015 and February 2016, 30 patients with primary OA with a mean age of 58 (41-71) years underwent THA with the Anato stem and Trident cup (Stryker, Mahwah, NJ, USA). The patients are part of an ongoing RSA project at Skåne University Hospital in Lund, Sweden [9,[18][19][20][21]. Patient inclusion criteria and demographics are summarized in Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%